Lawmaking under pressure : international humanitarian law and internal armed conflict - Mantilla, Giovanni, 1981- (Cornell University Press, 2020)
"This book explains the origins and development of the international humanitarian laws that exist to regulate internal armed conflict. It explains and documents the tense politics behind the making of these laws and explains how these were historically overcome under specific circumstances, thanks to the work of nongovernmental organizations and through social pressures among states, using extensive primary evidence, especially declassified archival sources from four countries (US, UK, France and Switzerland) and interviews"--